The variation of equatorial spread-F occurrences observed by ionosondes at Thailand longitude sector - Rungraengwajiake, Sarawoot; Supnithi, Pornchai; Tsugawa, Takuya; Maruyama, Takashi; Nagatsuma, Tsutomu (My University, 2013)
The equatorial spread-F (ESF) is a phenomenon of ionopheric irregularities which are mainly generated by the generalized Rayleigh-Taylor (R-T) instability mechanism in conjunction with the other physical mechanisms, originated at the bottom side of the F-layer in the equatorial region after sunset. It degrades the quality of signals that propagate through these irregularities, especially in the navigation satellite system, which requires the high integrity signals. In this work, we analyze the ESF statistics obtained from the FM/CW ionosonde stations over Thailand longitude sector. One is at Chumphon (10.72 N, 99.37 E, dip latitude 3.0), located near the geomagnetic equator, and the other station is located at Chiangmai (18.76 N, 98.93 E, dip latitude 12.7). Both stations are as part of the South-East Asia Low Latitude Ionospheric Network (SEALION) project. The ionograms are obtained at every 15 min from September 2004 to August 2005, which has the monthly mean of solar 10.7 cm flux (F10.7) from ∼80 to ∼110. In addition, we compare the diurnal patterns between the ESF occurrences and the variation of virtual height of the F-layer bottom side (h'F) of these two stations. The results show that the ESF occurrences at Chumphon stations are higher than Chiangmai station in all seasons. The high ESF occurrences of both stations mostly occur in equinoctial months corresponded with the rapid rising of the monthly mean h'F in the post-sunset. However, some inconsistent results are still observed, implying the role of other factors such as gravity waves and planetary waves to ESF occurrences. © 2012 COSPAR. Published by Elsevier Ltd. All rights reserved.
Keywords: Equatorial ionosphere; Equatorial spread-F; F-layer height